DER TRANSFORMATIONSPROZESS RUMÄNIENS UND SEINE HINDERNISSE ZUR DEMOKRATIE - STOENESCU, Roxana (Studia Universitatis Babes-Bolyai Studia Europaea, 2018)
The Transformation Process of Romania and Its Obstacles to Democracy. This article discusses the difficulties of Romania's transformation and democratisation process. Despite the "official" change of system, corruption, social inequality, clan structural organisation and nepotism prevail in Romania. Without democratic values having provided the decisive impetus for the transformation of society, the completion of the system change didn´t take place, because there was no basis for a democratic change of values. The main thesis is that if the consciousness of the broad masses, despite the formal democratisation process did not change fundamentally, changing towards a democratic identity remains rather a utopian goal.